Evaluation of Epidemiological Investigation 1 -2-5 Implementation Program in Sukabumi - Prasetyowati, Heni; Widawati, Mutiara; Fuadzy, Hubullah; Fuadiyah, M. Ezza Azmi; Ginanjar, Aryo; Nurindra, Rohmansyah W; Ridwan, Wawan; Hodijah, Dewi Nur; Sulaeman, Rizal Pratama (Indonesian Journal of Tropical and Infectious Disease, 2021)
Epidemiological investigations as part of the malaria surveillance system in Indonesia are carried out through the 1-2-5 method. Assessing the 1-2-5 strategy compliance level at the district level is the first step towards determining whether the surveillance and response strategy is working as planned or not. This study was conducted in order to determine whether PE 1-2-5 had been implemented in health centers (puskesmas) in malaria receptive areas according to the technical guidelines issued by the Indonesian Ministry of Health. Health centers were determined through purposive sampling technique. The sampling is determined by selecting health centers that have been doing malaria vector control service in 2018 and 2019. Ten Puskesmas in malaria receptive areas in Sukabumi District were selected. The informants in this study were the key players in the malaria program at the health centers: the head of the health centers, the manager of the malaria program, and the village malaria officer (JMD) who were involved in the vector control process in 2018 and 2019 at the selected health centers. Data collection was conducted through in-depth interviews done by researcher with informants. The interview showed that the malaria program personnel in Sukabumi are doing the strategy as best as possible in order to achieve malaria elimination. 1-2-5 surveillance program in Sukabumi district has been implemented even though the implementation is not as ideal as the technical guidelines suggested by the Indonesian Ministry of Health, Sukabumi district still applied the strategy based on it by adjusting various aspects (resource situation and the availability of facilities) to the suitable condition in Sukabumi.